Metastatic pancreatic neuroendocrine tumors feature elevated T cell infiltration - Jacques Greenberg; Jessica Limberg; Akanksha Verma; David Kim; Xiang Chen; Yeon J. Lee; Maureen D. Moore; Timothy M. Ullmann; Jessica W. Thiesmeyer; Zachary Loewenstein; Kevin J. Chen; Caitlin E. Egan; et al. (JCI Insight, 2022)
Pancreatic neuroendocrine tumors (PNETs) are malignancies arising from the islets of Langerhans. Therapeutic options are limited for the over 50% of patients who present with metastatic disease. We aimed to identify mechanisms to remodel the PNET tumor microenvironment (TME) to ultimately enhance susceptibility to immunotherapy. The TMEs of localized and metastatic PNETs were investigated using an approach that combines RNA-Seq, cancer and T cell profiling, and pharmacologic perturbations. RNA-Seq analysis indicated that the primary tumors of metastatic PNETs showed significant activation of inflammatory and immune-related pathways. We determined that metastatic PNETs featured increased numbers of tumor-infiltrating T cells compared with localized tumors. T cells isolated from both localized and metastatic PNETs showed evidence of recruitment and antigen-dependent activation, suggestive of an immune-permissive microenvironment. A computational analysis suggested that vorinostat, a histone deacetylase inhibitor, may perturb the transcriptomic signature of metastatic PNETs. Treatment of PNET cell lines with vorinostat increased chemokine CCR5 expression by NF-κB activation. Vorinostat treatment of patient-derived metastatic PNET tissues augmented recruitment of autologous T cells, and this augmentation was substantiated in a mouse model of PNET. Pharmacologic induction of chemokine expression may represent a promising approach for enhancing the immunogenicity of metastatic PNET TMEs.